Coding a Revolution. - Vaisman, Daria (Foreign Policy)
Three years ago, Iran decided to switch its government computer system to open-source software, which gave the Islamic Republic one of the most advanced groups of female coders anywhere in the world. A recent EU survey found that just 1.5 percent of European open-source coders are female, but in Iran, some estimates report that half of all software engineers coming out of the nation's universities are female. With the limits imposed on women in the Middle East, technology is an appealing option for those who desire a career: Technological work, and especially coding, can be done from home, permitting ambitious women to become well-known within their industry without offending their communities. Similar patterns are now appearing elsewhere in the region, such as Syria.